Polymer-conjugated bovine pancreatic and seminal ribonucleases inhibit growth of human tumors in nude mice - Poucková, P; Zadinová, M; Hlousková, D; Strohalm, J; Plocová, D; Spunda, M; Olejár, T; Zitko, M; Matousek, J; Ulbrich, K; Soucek, J (Journal of controlled release, 2004)
The hydrophilic poly[N-(2-hydroxypropyl)methacrylamide] (PHPMA) was used for RNase A or BS-RNase modification to prevent their degradation in bloodstream or fast elimination. Two PHPMA chains (classic and star-like) were synthesized and their conjugates with both enzymes were tested on the CD-1 nude mice bearing various human tumors. These RNase conjugates injected intravenously or intraperitoneally into the mice bearing melanoma, neuroblastoma or ovarian tumor caused significant reduction of transplanted tumors following ten daily doses of 2.5 and/or 1 mg/kg, respectively, while free RNase A or BS-RNase injected in doses of 10 mg/kg exerted only negligible antitumor activity. Histological examination confirmed potent cytotoxic effect of RNase A conjugates in ovarian tumor. Despite the antitumor activity observed in vivo, the in vitro cytotoxic activity of RNase A conjugates was not pronounced and did not differ from that caused by the free RNase A. The in vitro experiments with 125I-labeled preparations demonstrated that polymer conjugates were internalized by tumor cells very poorly in contrast to the dose-dependent internalization of the wild enzyme preparation. Surprisingly, mice injected with EL-4 leukemic cells, which were preincubated for 4 h with BS-RNase conjugates, exerted significantly prolonged survival compared with the control non-treated mice. It may be supposed that both BS-RNase and RNase A conjugates with PHPMA act after administration in vivo by a mechanism different from that or those occurring under in vitro conditions because in vivo they exert an antitumor action, whereas in vitro, they are ineffective. The experiments proved that RNase A, when conjugated to PHPMA, produced identical aspermatogenic and antitumor effects as BS-RNase conjugated to this polymer and that this preparation may be regarded as a potential anticancer drug.
Keywords: Female; polymery; protinádorové látky; Polymers; Ribonuclease, Pancreatic; myši; Animals; Cattle; Neuroblastoma; myši nahé; Methacrylates; teratogeny; Mice, Nude; Injections, Intravenous; pankreas; Pancreas; Ovarian Neoplasms; sperma; Enzyme-Linked Immunosorbent Assay; Humans; Ribonucleases; injekce intraperitoneální; Spermatogenesis; neuroblastom; nádory vaječníků; buněčné dělení; těhotenství; Teratogens; lidé; Cell Division; Mice; zvířata; Tumor Cells, Cultured; nádorové buňky kultivované; ribonukleasy; Semen; ELISA; ženské pohlaví; Antineoplastic Agents; pankreatická ribonukleasa; Neoplasm Transplantation; Pregnancy; Injections, Intraperitoneal; spermatogeneze; methakryláty; skot; injekce intravenózní; transplantace nádorů